225. Efficacy and safety of sulbactam-durlobactam are consistent across regions in the global ATTACK phase 3 trial in the treatment of carbapenem-resistant Acinetobacter baumannii-calcoaceticus complex (CRABC) infections. (15th December 2022) - Miller, Alita; Shapiro, Adam B; McLeod, Sarah; Rana, Khurram; Lewis, Drew; Altarac, David
Abstract: Background: ATTACK is a randomized, active-controlled, noninferiority trial that evaluated the efficacy and safety of sulbactam-durlobactam (SUL-DUR) compared to colistin for CRABC infections. The primary efficacy endpoint of all-cause mortality (ACM) at day 28 and the primary safety objective of incidence of nephrotoxicity based on RIFLE criteria were met. Due to the global variation of carbapenem and multi-drug resistance, geographic subgroups were evaluated to explore consistency of efficacy and safety across regions. Methods: Patients were randomized to SUL-DUR or colistin treatment for 7-14 days and all patients received imipenem/cilastatin as background therapy. The primary efficacy analysis in the CRABC population consisted of 125 patients: SUL-DUR (N=63) and colistin (N=62). The primary safety population included 177 patients who received any amount of drug. Secondary efficacy endpoints included ACM at day 14, clinical cure and microbiological favorable assessment at end-of treatment (EOT), test-of-cure (TOC) and late follow-up (LFU). Results are described geographically by the following regions: the Americas, Asia-Pacific and Europe. Results: Overall, ACM at day 28 in the SUL-DUR arm and colistin arm was 12/63 (19.0%) vs. 20/62 (32.3%), respectively; ACM at day 14 overall in the SUL-DUR arm and colistin arm was 4/63 (6.3%) vs. 12/62 (19.4%), respectively (Table 1). Day 28 ACM, and secondary endpoints were similar across the geographic regions and consistent with overall findings (Table 1). Criteria for RIFLE nephrotoxicity were met more often in the colistin arm than the SUL-DUR arm in all regions (Table 1). Conclusion: ACM, clinical outcomes, microbiological favorable assessment, and RIFLE-assessed nephrotoxicity were consistently favorable in patients treated with SUL-DUR versus colistin across regions. These findings suggest, that if approved, SUL-DUR could be an important global therapeutic option for Acinetobacter infections including carbapenem-resistant and multidrug-resistant strains. Disclosures: Alita Miller, PhD, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Adam B. Shapiro, Ph.D, Entasis Therapeutics: Employee|Entasis Therapeutics: Stocks/Bonds Sarah McLeod, PhD, Entasis Therapeutics: Employee|Entasis Therapeutics: Stocks/Bonds Khurram Rana, PharmD, Entasis Therapeutics: Employee|Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Drew Lewis, MD, MTM&H, Entasis Therapeutics: employee|Entasis Therapeutics: employee|Entasis Therapeutics: Stocks/Bonds|Entasis Therapeutics: Stocks/Bonds David Altarac, MD, MPA, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds.